2003
DOI: 10.1038/sj.ijo.0802301
|View full text |Cite
|
Sign up to set email alerts
|

Body size from birth to adulthood as a predictor of self-reported polycystic ovary syndrome symptoms

Abstract: OBJECTIVE:To study the association between body size from birth to adulthood and self-reported symptoms of polycystic ovary syndrome (PCOS), particularly hirsutism and menstrual disturbances. DESIGN: Longitudinal, population-based study of a cohort of women born in 1966 in northern Finland. The study population included 2007 women who were not pregnant and did not use hormonal contraception. Of these 528 (26%) had self-reported symptoms of PCOS. RESULTS: Weight at birth, gestational age, being small for gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
2
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 35 publications
8
94
2
5
Order By: Relevance
“…More recently, human studies (Jarvelin et al, 1997;Laitinen et al, 2003 and have demonstrated that body shape at birth, rather than weight Litten-Brown, Corson and Clarke per se, may be a better indicator of future health and development of the human infant. The modern domestic pig, rather than the ancient domestic pig or minipig, is an excellent model for developmental programming due to the 2-to 3-fold variation in BW among littermates, which provides a naturally occurring form of foetal growth restriction with less genetic variation than seen in man or other monotocous species (Bauer et al, 1998;Corson et al, 2008a).…”
Section: Litten-brown Corson and Clarkementioning
confidence: 99%
“…More recently, human studies (Jarvelin et al, 1997;Laitinen et al, 2003 and have demonstrated that body shape at birth, rather than weight Litten-Brown, Corson and Clarke per se, may be a better indicator of future health and development of the human infant. The modern domestic pig, rather than the ancient domestic pig or minipig, is an excellent model for developmental programming due to the 2-to 3-fold variation in BW among littermates, which provides a naturally occurring form of foetal growth restriction with less genetic variation than seen in man or other monotocous species (Bauer et al, 1998;Corson et al, 2008a).…”
Section: Litten-brown Corson and Clarkementioning
confidence: 99%
“…25,62 On the other hand, a survey of a large population in the north of Finland concluded that there was no association between birth weight and symptoms of PCOS in adolescents and adults. 63 For the time being then, it is important to keep an open mind about the possible non-genetic, intrauterine factors that could impact on development of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…During the third decade of life, this risk can be twice as high in women born SGA as it is in women born AGA (Melo et al 2010). However, PCOS does not occur in all women born SGA (Laitinen et al 2003, Mumm et al 2013, and …”
Section: )mentioning
confidence: 99%
“…Although SGA women in Brazil (Melo et al 2010) and those with LBW in Italy (Pandolfi et al 2008) and Turkey (Hizli et al 2012) present a higher risk for developing PCOS, these findings were not confirmed in individuals from the USA (Legro et al 2010), UK (Cresswell et al 1997, Michelmore et al 2001, Shayeb et al 2014, The Netherlands (Sadrzadeh et al 2003), Finland (Laitinen et al 2003), Spain (Ibáñ ez et al 2008) or Denmark (Mumm et al 2013). One study conducted in Australia analysed birth weight as a continuous variable and found that each 100 g increase in birth weight increased the risk of hyperandrogenism.…”
Section: Genetic Predispositionmentioning
confidence: 99%
See 1 more Smart Citation